Impact of Supply Chain Strategy on Final Micro, Small, and Medium Enterprises Income Tax Tariff Change to Income Tax Revenue (Study in Kendari Tax Service Office) - Hasbudin Hasbudin; Ika Maya Sari; Tuti Dharmawati; Inten Sri Mulyani (International Journal of Supply Chain Management, 2020)
Abstract- This study aimed to determine the impact of the supply chain strategy in the final income tax rate of micro, small, and medium-sized enterprises on the income tax revenue. Method of collecting its data were conducted by documentation and interview. Data analysis method via descriptive analysis was conducted with interactive models. The result of this study showed that when changing the final income tax rate of micro, small and medium-sized enterprises from 1% to 0,5%, it has made a reduction on its final income tax revenue 6 months after the change in the final income tax rate is being applied. The supply chain management changes in the final income tax rate also made an impact in enhancing the number of tax-payers (coming from micro, small and medium-sized enterprises) in the city of Kendari.